DISKURSUS PENERAPAN SYARIAT ISLAM DI INDONESIA: Perspektif Filosofis, Yuridis dan Syar’i - Hartono, Hartono (Ekonomi Syariah STAI Sangatta Kutai Timur, 2019)
Islam syari’ah, fiqh and islamic law have always been an interesting academic discussion, something more like that. In this text on the islamic syariate is the most analyzed. More over the matter has come to light around us. The presence of several civil society organization who want to establish and implement the islamic faith on earth in Indonesia is a real fact. Dialectics, debate and dialogue on Islamic shari'ah and its application in Indonesia become an unrelenting topic to be discussed and studied, a democratic environment that gives freedom and openness to competition for various ideas to provide the widest possible space for all of them, the birth of name control on Fundamental Islam, Liberal Islam, Moderate Islam, Actual Islam, Transformative Islam, Progressive Islam, Inclusive Islam and Accommodative Islam, all of that is an expression in seeing contemporary Islam, which is considered to be able to represent and interpret existing Islam.